Bullying in Elementary Schools: A Systematic Literature Review from 2014 to 2024 - Arif, Muhamad; Chapakiya, Suraiya; Sakdiyah , Nur Halimatus (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2024)
A black mark that must be erased is the phenomenon of bullying in the field of education. The results of a variety of research studies on bullying behavior in elementary school children have prompted researchers to conduct a critical analysis with three research focuses: 1) the factors that contribute to the occurrence of bullying in elementary schools; 2) the bullying behaviors in elementary schools; 3) the strategies that elementary schools employ to address bullying among students. In order to accomplish these objectives, a systematic literature review was implemented through bibliographic mapping and visualization, which were derived from bibliometrics derived from the results of the literature analysis in the form of PRISMA analysis. The findings indicate that internal and external factors influence bullying behavior. In the interim, bullying behavior manifests as physical, verbal, and nonverbal violence. Consequently, educational institutions implement a variety of strategies, including institutional and individual strategies.